Laparoscopic Sentinel Lymph Node Mapping Using NIR Fluorescence with ICG in Early Endometrial Cancer: Experience at a Tertiary Care Oncology Centre - Bhati, Priya; Gupta, Saumya; Garg, Monal; Puthenveettil, Nitu; Nair, Indu R; Rajanbabu, Anupama (Asian Pacific Journal of Cancer Biology, 2023)
Objective: To determine the detection rates and location of sentinel nodes as well as to determine intraoperative and postoperative surgico-pathological outcomes in endometrial cancer patients who underwent laparoscopic staging with sentinel node biopsy using ICG dye. Materials and Methods: This retrospective study was conducted in a tertiary care oncology centre, Amrita Institute of medical sciences, Kochi from April 2021 to March 2023. All cases of biopsy proven early stage endometrial carcinoma that underwent laparoscopic staging with SLN mapping using the ICG dye were included. All histological types were included, as long as the disease was confined to the uterus, clinically and on MRI. Results: A total of 80 patients were found eligible for the study. Only the patients with apparent uterine confined disease on preoperative MRI were selected for sentinel mapping, 80 % of whom had IA disease on MRI, and 20 % had IB, 13.5 % were high grade histology.The overall SLN detection rate was 93.75%, and bilateral detection rate was 92.5 %. Most common location was external iliac in 40.8% cases. Only 1 patient was found to harbour nodal micro metastasis on ultrastaging. Final histopathology identified stage IA in 63 (78.75%) patients, IB in 14 (17.5%), Stage II in 2 (2.5%) and Stage IIIC1 in 1 (1.25%) patient. Conclusion: Laparoscopic staging with SLNB using ICG is a practicable approach for uterine limited disease on preoperative evaluation. It extends the benefits of minimally invasive surgery to these patients, while overcoming the limitations of prohibitive cost or availability of expensive robotic equipment.